2003
DOI: 10.1076/ceyr.26.5.313.15440
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of porcine cornea as xenograft

Abstract: Porcine corneal stroma induces no hyperacute rejection but mild cellular rejection when transplanted in the cornea of cynomolgus monkeys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 10 publications
4
37
2
Order By: Relevance
“…As early as 2003, Amano et al suggested that heterogeneous corneal stromas, especially porcine corneal stromas, could be ideal alternatives to human corneas due to their lower antigenicities, as demonstrated in in vitro corneal tissue engineering, and transparently healing, as shown in animal experiments (16). In addition, studies regarding the successful construction of tissue-engineered hearts, lungs, and livers using acellular biomaterials have also been reported (17)(18)(19), which indicates that the acellular stroma is a suitable carrier for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…As early as 2003, Amano et al suggested that heterogeneous corneal stromas, especially porcine corneal stromas, could be ideal alternatives to human corneas due to their lower antigenicities, as demonstrated in in vitro corneal tissue engineering, and transparently healing, as shown in animal experiments (16). In addition, studies regarding the successful construction of tissue-engineered hearts, lungs, and livers using acellular biomaterials have also been reported (17)(18)(19), which indicates that the acellular stroma is a suitable carrier for tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, xenogeneic models may procure similar biomechanical properties to the human cornea. 31 Previous studies have shown for various organs that decellularization is a suitable way to obtain nonimmunogenic and functional xenografts for transplantation. [17][18][19][20][21][22][23][24][25] The current worldwide donor shortage may theoretically be diminished or even obliterated by tissue engineering.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have found that the ␣ -gal epitope, which induces hyperacute rejection, is almost absent in the porcine cornea except for several keratocytes in the anterior-most part [Amano et al, 2003]. Several studies have reported that no endogenous retrovirus infection was detected in any patient treated with various living pig parts [Patience et al, 1998;Paradis et al, 1999].…”
Section: Discussionmentioning
confidence: 99%